Entomological authentication of honey based on DNA markers: differentiation of honey produced by Apis mellifera and Apis cerana - Amaral, Joana S. (2019)
According to the European Union legislation, honey is the natural sweet substance produced by Apis mellifera, also known as European honeybee. However, in other regions of the world, honey is traditionally obtained from other bee species. Among those, A. cerana (also known as Asian honeybee) is also of economic importance since it is used in apiculture. Due to the decline of the wild populations of the A. cerana in some countries, such as Japan and parts of China, there is an increasingly interest in preserving the native Asian honeybee, being its honey increasingly valued. Owing to the growing demand for this traditional product, the honey produced by A. cerana attains a much higher market value compared to that of A. mellifera, thus being prone to adulteration. So far, only a few protein-based methods have been proposed to assess honey entomological origin [1], which in fact is related to its geographical origin since bee species generally occupy different geographical ranges according to their evolutionary lineages [2]. In this work, DNA methods were developed for the specific identification of A. mellifera and A. cerana DNA in honey. For this purpose, bees of A. cerana from Thailand, China and Vietnam and honeybees of 4 different subspecies of A. mellifera (iberiensis, mellifera, ligustica and carnica) from EU countries were used. Different sets of primers were designed targeting the tRNAleu - COII intergenic region and the 16S rRNA gene. For both cases, the specificity and sensitivity of the designed primers were assayed by qualitative polymerase chain reaction (PCR). DNA was extracted from honey samples as previously described [3]. PCR with primers targeting the tRNAleu - COII intergenic region allowed the specific detection of A. cerana. The applicability of the proposed new PCR method was assayed with authentic A. cerana and A. mellifera honey samples, which enabled the identification of A. cerana honey. PCR targeting the 16S rRNA gene successfully amplified both honeybee species, but without being able to differentiate them. However, the use of real-time PCR with 16S rRNA primers coupled with High Resolution Melting (HRM) analysis allowed the differentiation of both species in distinct clusters (Fig. 1). The developed new HRM methodology was further applied to the analysis of authentic honey samples from Vietnam (produced from A. cerana and A. mellifera honeybees) and from Portugal (produced from A. mellifera honeybees), as well as commercial samples of honey labelled as produced in the EU, allowing its successful entomological origin identification [4]. Both developed techniques proved their effectiveness for establishing the entomological origin of honey and can be considered as useful tools for authentication/control purposes.